GENETIC DIVERGENCE ALONG THE SPECIATION CONTINUUM: THE TRANSITION FROM HOST RACE TO SPECIES IN RHAGOLETIS (DIPTERA: TEPHRITIDAE). (29th July 2013) - Powell, Thomas H. Q.; Hood, Glen R.; Murphy, Mason O.; Heilveil, Jeffrey S.; Berlocher, Stewart H.; Nosil, Patrik; Feder, Jeffrey L.
Abstract : Studies of related populations varying in their degrees of reproductive isolation can provide insights into speciation. Here, the transition from partially isolated host races to more fully separated sibling species is investigated by comparing patterns of genetic differentiation between recently evolved (∼150 generations) apple and ancestral hawthorn‐infesting populations of Rhagoletis pomonella to their sister taxon, the undescribed flowering dogwood fly attacking Cornus florida . No fixed or diagnostic private alleles differentiating the three populations were found at any of 23 microsatellites and 10 allozymes scored. Nevertheless, allele frequency differences were sufficient across loci for flowering dogwood fly populations from multiple localities to form a diagnosable genotypic cluster distinct from apple and hawthorn flies, indicative of species status. Genome‐wide patterns of differentiation were correlated between the host races and species pair comparisons along the majority of chromosomes, suggesting that similar disruptive selection pressures affect most loci. However, differentiation was more pronounced, with some additional regions showing elevated divergence, for the species pair comparison. Our results imply that Rhagoletis sibling species such as the flowering dogwood fly represent host races writ large, with the transition to species status primarily resulting from increased divergence of the same regions separating apple and hawthorn flies.